STUDI TENTANG KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS CIAWI KABUPATEN BOGOR - Munispa, Siti; Amri, Chairul; Rahmawati, Rita (JURNAL GOVERNANSI, 2016)
Community Health Centres (Puskesmas) is the primary health care system that serves patients in general and patients with health insurance card (BPJS). Low cost is the reason that community choose Puskesmas as the first choice for medical treatment. However, there are many patients who complain about the lack of quality health services on Puskesmas. Therefore, the purpose of this study was to determine the quality of health service on Puskesmas. This study took place in Puskesmas Ciawi, Bogor Regency, West Java, Indonesia. The research used descriptive method and qualitative approach. Data was collected by bibliography study, observation, and interview. The results showed that the quality of health care on Puskesmas Ciawi still has some drawbacks, namely a less comfortable lounge area, a limited number of toilets, the less friendly clerk. Most community health service users view the service of process than the outcome and image. Therefore, the results of this study recommend that the quality of health care is determined by the ability of management and hospital medical committee including head of  Puskesmas in maintaining the reputation of the institution and the public trust.     Key words: Service Quality, Health Center, Reputation Institute, a medical committee